CHM561: Quality in Analytical Measurement / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2023)
This course will interactively engage students cognitively and scientifically in areas of sampling, method selection, procedures in establishing new analytical process, validating an analytical method, making and reporting measurements, quality assurance issues in making analytical measurement and reporting for efficient management of analytical laboratories. Quality and reliability are the two very important parameters in analytical chemistry. High-quality analytical information alone is not enough, as the information must also be reliable. Reliability is defined as the maintenance of quality through time. To obtain reliable analytical data, it is important to examine the reliability of all the steps involved in analytical process: sampling, data processing and reported results. Topics such as quality systems in chemical laboratories will facilitate the mutual recognition of analytical data between laboratories and trading partners in relation to regulations. The outcomes shall be accessed through a variety of tools which include the final examination and tests.